2013
DOI: 10.3892/br.2013.133
|View full text |Cite
|
Sign up to set email alerts
|

Expression of set is downregulated by rapamycin in human colorectal cancer cells

Abstract: Abstract. The purpose of this study was to determine the mechanism through which rapamycin treatment affects the expression of the set gene in human colorectal adenocarcinoma cells. The effect of rapamycin treatment on set expression was evaluated by assessing the mRNA and protein expression of set in the SW480 and LoVo human colon carcinoma cell lines following treatment with rapamycin by quantitative polymerase chain reaction (qPCR) and western blot analysis, respectively. Our results demonstrated that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It has been well established that mTOR pathway plays an essential role in the development and progression of CRC 30 , 31 . As mTOR inhibitors, temsirolimus and everolimus had been approved by FDA for the treatment of patients with metastatic renal cell carcinoma 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that mTOR pathway plays an essential role in the development and progression of CRC 30 , 31 . As mTOR inhibitors, temsirolimus and everolimus had been approved by FDA for the treatment of patients with metastatic renal cell carcinoma 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…As mTOR inhibitors, temsirolimus and everolimus had been approved by FDA for the treatment of patients with metastatic renal cell carcinoma 32 , 33 . Although rapamycin (sirolimus) was usually used as immunosuppressant for organ transplantation 34 , the role of rapamycin in inhibiting the protein kinase activity of mTOR and anitproliferative ability makes it a potential anticancer agent 30 , 31 . Preclinical studies have suggested that the combination of rapamycin with a VEGF antibody or trastuzumab exhibited a synergistic antitumor effect in a pancreatic or breast cancer model, respectively 35 , 36 .…”
Section: Discussionmentioning
confidence: 99%